2016
DOI: 10.1139/cjas-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Variation in fur farm and wild populations of the red fox, Vulpes vulpes (Carnivora: Canidae) — Part I: Morphometry

Abstract: This paper demonstrates the influence of artificial selection on morphometric traits in the red fox [Vulpes vulpes (Linnaeus, 1758)]. Measurements and two proportion coefficients were analysed in 132 wild and 199 farm red foxes. The two groups differed significantly (P ≤ 0.05) on all but one of the measurements. Eight out of 11 measurements were significantly greater in the farm fox population, while only tail length, ear height, and length of the right hind limb were greater in the population of wild foxes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…If the farm population originated from North American red foxes, then the admixture analysis would show a higher level of non‐native alleles (imported from North America) and a lack or low level of alleles of Eurasian origin. Earlier morphological studies and preliminary results of microsatellite markers analysis (Zatoń‐Dobrowolska et al., , ) have suggested that the origin of foxes and selective breeding played a significant role in the differentiation of morphological traits in Polish farm‐ and wild red foxes. However, to the best of our knowledge, only Jeżewska‐Witkowska et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the farm population originated from North American red foxes, then the admixture analysis would show a higher level of non‐native alleles (imported from North America) and a lack or low level of alleles of Eurasian origin. Earlier morphological studies and preliminary results of microsatellite markers analysis (Zatoń‐Dobrowolska et al., , ) have suggested that the origin of foxes and selective breeding played a significant role in the differentiation of morphological traits in Polish farm‐ and wild red foxes. However, to the best of our knowledge, only Jeżewska‐Witkowska et al.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive comparative research taking into account both morphological traits and molecular markers (microsatellites and mtDNA) has recently been carried out by Zatoń‐Dobrowolska et al. () and Zatoń‐Dobrowolska, Moska, Mucha, Wierzbicki, and Dobrowolski (), who investigated the effect of ancestry and selective breeding on morphological differences between wild‐ and farm‐bred red fox populations in Poland. They found significant differences among the vast majority of the body, cranial and dental measurements studied.…”
Section: Introductionmentioning
confidence: 99%
“…Selective breeding carried out on farms prefers rather those phenotypes that bring economic profit for breeders (De Vries 1989;Wierzbicki 2005;Wierzbicki et al 2007). Due to different natural and artificial selection pressures phenotypic variation in different traits of the same species (e.g., V. vulpes, Neovison vison) may be induced (Melero et al 2012;Zatoń-Dobrowolska et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of that, it must be kept in mind that when we compare the wild population of European red foxes with farm red foxes, in fact we compare two genetically distinct populationsthe Eurasian red fox population vs. the red foxes of North American origin (a founder population of farm foxes which genetic structure has been changed through selective breeding). Thus, the morphological differences between wild and farm-bred foxes may have been caused, among others, by distinct gene pools of both populations (Zatoń-Dobrowolska et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation